An update on topical haemostatic agents in liver surgery: systematic review and meta analysis. (31st August 2016) - Brustia, Raffaele; Granger, Benjamin; Scatton, Olivier
Abstract: Mortality and morbidity in hepatic surgery are affected by blood loss and transfusion. Topical haemostatic agents (THA) are composed by a matrix and/or fibrin sealants, and their association known as "carrier‐bound fibrin sealant" (CBFS): despite widely used for secondary haemostasis, the level of evidence remains low. To realize a meta‐analysis on the results of CBFS on haemostasis and postoperative complications. Searches in PubMed, PubMed Central, Cochrane and Google Scholar using keywords: "topical_haemostasis" OR "haemostatic_agents" OR "sealant_patch" OR "fibrin_sealant" OR "collagen_sealant" AND "liver_surgery" OR "hepatic_surgery" OR "liver_transplantation". Randomized clinical trials, large retrospective cohort studies, case control studies evaluating THA on open/laparoscopic liver surgery and transplantation. From 1993 to 2016 were found 22 studies for qualitative synthesis and 13 for quantitative meta‐analysis. The time to haemostasis was lower in the CBFS group (mean difference −2.33 min; P  = 0.00001). The risk of receiving blood transfusion, developing collections and bile leak was not influenced by the use of CBFS (OR 0.75; P  = 0.25), (OR 0.72; P  = 0.52), (OR 0.74; P  = 0.30) respectively. The use of CBFS in liver surgery significantly reduce the time to haemostasis, but does not decrease transfusion, postoperative collection and bile leak.